2015
DOI: 10.1021/acs.nanolett.5b02205
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Crystalline/Amorphous Co/Co3O4 Core/Shell Nanosheets as Efficient Electrocatalysts for the Hydrogen Evolution Reaction

Abstract: Earth-abundant, low-cost electrocatalysts with outstanding catalytic activity in the electrochemical hydrogen evolution reaction (HER) are critical in realizing the hydrogen economy to lift our future welfare and civilization. Here we report that excellent HER activity has been achieved with three-dimensional core/shell Co/Co3O4 nanosheets composed of a metallic cobalt core and an amorphous cobalt oxide shell. A benchmark HER current density of 10 mA cm(-2) has been achieved at an overpotential of ∼90 mV in 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
254
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 489 publications
(277 citation statements)
references
References 50 publications
20
254
0
Order By: Relevance
“…This indicated that oxygen vacancy alone could not guarantee the high catalytic activity. Therefore, it was very likely that the surface-defective amorphous NiO shell lowered the HER energy barrier [42].…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that oxygen vacancy alone could not guarantee the high catalytic activity. Therefore, it was very likely that the surface-defective amorphous NiO shell lowered the HER energy barrier [42].…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, the platinum-based catalyst is still the best HER electrocatalyst under alkaline conditions due to the low onset overpotential, small Tafel slope and strong durability [7]. Although many non-noble-metal electrocatalysts such as Ni-based alloys [8][9][10][11][12] and Co-based nanocomposites [13][14][15] have motivated intense research on electrocatalytic HER, their poorer HER performance than Pt-based catalysts enormously restricts their practical applications. Consequently, how to enhance the HER activity of Pt-based materials in basic media is a greatly valuable but very challenging project.…”
Section: Introductionmentioning
confidence: 99%
“…[106] Co 3 O 4 Similar to the changes induced on NiO nanosheets, hydrogenation is also shown to convert Co 3 O 4 nanosheets to Co/Co 3 O 4 crystalline/amorphous core/shell nanosheets. [107] These Figure 7. (a) Schematic illustration of the hydrogenation-induced structural change from Ni x CeO 2+x to Ni/CeO 2 on carbon nanotubes.…”
Section: Mnmoomentioning
confidence: 99%
“…[107] Oxygen vacancies however, cause a poor performance. Typical microscopy images and the catalytic activity of the hydrogenated Co/ Co 3 O 4 nanosheets are shown in Fig.…”
Section: Mnmoomentioning
confidence: 99%
See 1 more Smart Citation